Dinamika Pertumbuhan Ekonomi Wilayah Dengan Pendekatan Analisis Shift Share di Provinsi Sulawesi Selatan - Djoko Indra Adhy; Nurul Anwar (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The present study has been conducted for the purpose of analysing the magnitude of changes in Gross Regional Domestic Revenue (GRDP) in South Sulawesi based on the components of National Share (NS), Industry Mix (IM) and Regional Shift (RS) by economic sectors, and determining the leading sectors of South Sulawesi Province. The methodology employed in this study involves the implementation of a shift share analysis, encompassing three distinct approaches: the classic approach, the Esteban-Marquillas approach, and the Arcelus modification. The analysis draws upon data pertaining to Indonesia's Gross Domestic Product (GDP) and South Sulawesi Province's GRDP for the period 2021-2023.The findings of the study indicate that South Sulawesi's economic growth is predominantly influenced by national economic developments. Despite its status as the leading sector, the agricultural sector has a net shift of IDR 1,868.50 billion. This is included in the slow growth category. The sector of the economy responsible for the highest net shift in output was that of accommodation and food services. In order to maximise economic growth, it is recommended that local governments focus on the development of economic sectors that are classified as competitive and fast-growing. Such sectors include corporate services and the provision of accommodation and food services, which have comparative and competitive advantages and are able to absorb a significant amount of labour.